2016
DOI: 10.15585/mmwr/mm6521a4
|View full text |Cite
|
Sign up to set email alerts
|

Notes from the Field: Investigation of Hepatitis C Virus Transmission Associated with Injection Therapy for Chronic Pain — California, 2015

Abstract: On November 26, 2014, the California Department of Public Health (CDPH) contacted CDC concerning a report from the Santa Barbara County Public Health Department (SBPHD) regarding acute hepatitis C virus (HCV) infection in a repeat blood donor. The patient, who was asymptomatic, was first alerted of the infection by the blood bank and had no traditional risk factors for HCV infection. The donor had a negative HCV nucleic acid test (NAT) 56 days before the first positive NAT test, and an investigation into the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…4 Iatrogenic HCV transmission has been reported in various outpatient settings, including hospitals and clinics for alternative medicine, cardiology, dialysis, endoscopy, insulin infusion, pain management, oncology, and prolotherapy. [5][6][7][17][18][19][20][21][22][23] The known or suspected mode of transmission includes syringe reuse, fingerstick device reuse, single-dose vial reuse, infection control lapses in medication preparation, drug diversion, and breaches in environmental cleaning and disinfection practices. 17,18 Adherence to injection safety procedures would effectively eliminate this transmission risk.…”
mentioning
confidence: 99%
“…4 Iatrogenic HCV transmission has been reported in various outpatient settings, including hospitals and clinics for alternative medicine, cardiology, dialysis, endoscopy, insulin infusion, pain management, oncology, and prolotherapy. [5][6][7][17][18][19][20][21][22][23] The known or suspected mode of transmission includes syringe reuse, fingerstick device reuse, single-dose vial reuse, infection control lapses in medication preparation, drug diversion, and breaches in environmental cleaning and disinfection practices. 17,18 Adherence to injection safety procedures would effectively eliminate this transmission risk.…”
mentioning
confidence: 99%
“…Four other persons who underwent procedures at the clinic on the same day were also subsequently identified to have HCV infection. Multiple other health care-associated outbreaks of HCV infection resulting from unsafe injection practices have been documented by CDC during 2008–2015 [18]. On the other hand, the largest increase in HCV observed in this study, a 127% increase from 0·52% to 1·18%, was in the Port-au-Prince region between 2010 and 2013, in the years following Haiti’s devastating 2010 earthquake.…”
Section: Discussionmentioning
confidence: 62%
“…Although outbreaks of HBV 23 and HCV 13,14,24,[30][31][32] related to unsafe injection practices are infrequently recognized, unsafe injection practices have been described in a sizeable minority of health settings. In one survey, 43% of 370 physicians from 8 states reported that healthcare personnel in their workplace reentered multidose vials with the same syringe for an additional dose for the same patient; yet only 26% of physicians reporting this practice indicated that multidose vials are never used for >1 patient in their workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Injection safety breaches similar to those described in this report have been associated with clusters of HBV 23 and HCV. 13,14,24,[30][31][32] The CDC has developed resources and recommendations for clinicians to ensure that safe injection practices are used in all healthcare settings. 37 Relevant recommendations include not entering medication vials with a used syringe and dedicating single-dose vials for 1 patient only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation